2018
DOI: 10.14581/jer.18013
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Its Determinants in Adult Drug Refractory Epilepsy Patients Who Were Not Candidates for Epilepsy Surgery: A Correlational Study

Abstract: Background and Purpose This study was performed to elucidate quality of life (QOL) and its determinants in adult drug refractory epilepsy (DRE) patients who were not candidates for epilepsy surgery. Methods A correlational study was performed at the center of excellence, epilepsy between July 2014 to June 2016. All consecutive DRE patients who were not candidates for epilepsy surgery were enrolled. The outcomes were QOL, assessed using the quality of life inventory in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Since that review, several single‐center studies have assessed the relationship of QoL with DRE; however, these studies were conducted outside of the United States and did not take a comprehensive multivariate approach including HCRU 6,8,19,20 . In addition, one of the studies focused only on patients with focal epilepsy.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Since that review, several single‐center studies have assessed the relationship of QoL with DRE; however, these studies were conducted outside of the United States and did not take a comprehensive multivariate approach including HCRU 6,8,19,20 . In addition, one of the studies focused only on patients with focal epilepsy.…”
Section: Significancementioning
confidence: 99%
“…Advancements in antiepileptic drug (AED) treatments have resulted in the potential for the complete remission of seizures in patients with epilepsy 1 . However, approximately 30%–40% of adult patients have drug‐resistant epilepsy (DRE; defined as failure to achieve sustained seizure remission despite adequate trials of two appropriately chosen and used AEDs), and continue to experience seizures despite multiple treatment attempts, 2–5 resulting in a significant economic burden and decrease in quality of life (QoL) for patients and their caregivers 5–8 …”
Section: Introductionmentioning
confidence: 99%
“…This is in line with a previous study that found patients with drug refractory epilepsy were worried about the long-term side ef-fects of the drugs on their body. 12 Additionally, they were concerned about changing type/strength of medication, medication ineffectiveness, and feeling bored with taking medication every day (item scores of 3.5). Therefore, healthcare providers should take more care of these concerns of patients to enhance their medication therapy-related quality of life.…”
Section: Medication-related Quality Of Lifementioning
confidence: 99%
“…Little was also known about associations between medication-related quality of life and patient characteristics in epilepsy patients since most previous studies assessed the relationships with health-related quality of life, non-specific medication measures. [4][5][6][12][13][14][15] Hence, the second objective was to evaluate such associations. This information will be helpful for healthcare providers to manage medication therapy for epilepsy patients.…”
Section: Introductionmentioning
confidence: 99%
“…Drug-resistant epilepsy (DRE) poses an increased risk of hospitalizations, medication non-adherence, and poor quality of life (QoL) [1][2][3][4][5][6][7][8][9][10][11]. A multitude of factors could account for why patients have unaddressed DRE, such as gaps in disease education, socioeconomic and societal limitations to healthcare access, lack of care-giver involvement, and healthcare provider (HCP) reluctance to move beyond pharmacological therapies, among others [12,13].…”
Section: Introductionmentioning
confidence: 99%